PEDESTRIAN PATHS UTILIZATION: SAFETY AND ATTRACTIVENESS ASPECTS (Case Study: Ir. H Juanda Raya Sidewalk, Depok, Indonesia) - Airlambang, Sutrysno; Popi Puspitasari (Jurusan Arsitektur - FTSP - Universitas Trisakti, 2021)
Sidewalks are supporting facilities for traffic management, crossings, and people's traffic. In the case studied, it was found that part of the space on the pedestrian path was used by informal traders, for trading or other activities so that the utilization of the pedestrian path was not optimal. This study aims to reveal the utilization of Ir. Juanda Street Corridor in Depok City, related to safety and attractiveness aspects, using a quantitative descriptive method. Data was collected through questionnaires and field observations, followed up with data processing through SPSS. The results showed that the safety factor of pedestrians on the sidewalks of Ir Juanda street, Depok City was relatively low. This is indicated by the emergence of fear of criminal action due to the behavior of street vendors which is reinforced by poor physical quality. Ornamental plant traders, easy access to parking lots, and temporary market activities are aspects of the attraction, although on the other hand the presence of informal traders on the sidewalk is considered a nuisance. Keywords: Pedestrian path, safety, attractiveness